2008
DOI: 10.1634/theoncologist.2008-0173
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Drug Resistance Genes into Hematopoietic Stem Cells for Marrow Protection

Abstract: The study investigates the use of gene transfer with genes that confer drug resistance for the purpose of bone marrow protection from chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…O 6 BG has been in clinical trials in a variety of cancers (brain, breast and melanoma), mainly to increase the efficacy of anticancer alkylating agents such as temozolomide and BCNU; in these cases, it is well established that specific inhibition of MGMT by O 6 BG results in increased number of DNA crosslinks and, in turn, an enhanced alkylator efficacy. We are aware that myelosuppression is a major limitation in the clinical trials involving O 6 BG with alkylating agents, and this problem can be overcome by gene therapy efforts of transducing O 6 BG-resistant mutant MGMT into the hematopoietic stem cells, thus affording selective protection to hematopoietic stem cells (36,37). Recent studies have also shown that O 6 BG can increase the efficacy of cisplatin, cyclophosphamide, and nonalkylators like camptothecin, but the mechanisms involved are currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“…O 6 BG has been in clinical trials in a variety of cancers (brain, breast and melanoma), mainly to increase the efficacy of anticancer alkylating agents such as temozolomide and BCNU; in these cases, it is well established that specific inhibition of MGMT by O 6 BG results in increased number of DNA crosslinks and, in turn, an enhanced alkylator efficacy. We are aware that myelosuppression is a major limitation in the clinical trials involving O 6 BG with alkylating agents, and this problem can be overcome by gene therapy efforts of transducing O 6 BG-resistant mutant MGMT into the hematopoietic stem cells, thus affording selective protection to hematopoietic stem cells (36,37). Recent studies have also shown that O 6 BG can increase the efficacy of cisplatin, cyclophosphamide, and nonalkylators like camptothecin, but the mechanisms involved are currently unclear.…”
Section: Discussionmentioning
confidence: 99%
“…There are no clinical data yet to suggest that MDR can be completely reversed using this RNA interference (RNAi) technology, but it is likely that drugs related to RNAi will be developed in the near future. (iv) Transferring MDR genes into NSCs, especially bone marrow stem cells (133)(134)(135). Most chemotherapeutic drugs suppress the bone marrow and, as a result, blood cells such as erythrocytes, leukocytes, and thrombocytes do not function properly, and the ensuing loss of oxygen transport, immune response, and bleeding control functions causes serious adverse effects.…”
Section: Future Perspectivesmentioning
confidence: 99%